THE INFLUENCE OF INVESTMENT DECISIONS, FREE CASH FLOW, AND DEBT POLICY ON THE FINANCIAL PERFORMANCE OF CONSTRUCTION COMPANIES - Firmansyah, Akhmad Andri; Sahab, Muhammad Tri Zulfi; Wisudanto, Wisudanto (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
The construction industry plays a pivotal role in any country's economy, driven by the increasing demand for infrastructure, housing, and facilities during periods of rapid economic growth. Efficient financial management is paramount for construction companies to ensure sustainability and growth. This study explores the impact of investment decisions, free cash flow, and debt policy on the financial performance of construction companies. Investment decisions significantly affect financial performance as they influence the allocation of resources, with an emphasis on the Price Earning Ratio (PER) to gauge market expectations and future prospects. Free cash flow, representing the cash available after operational and investment costs, positively and significantly affects financial performance. Debt policy, as a crucial part of capital structure decisions, also significantly influences financial performance. The study uses quantitative methods and concludes that these factors collectively explain 62.9% of the variation in financial performance. Understanding these dynamics can aid construction companies, investors, regulators, and other stakeholders in optimizing financial strategies and achieving sustainable growth in the competitive construction industry.